Hambatan dalam Pembangunan Kawasan Perdesaan Agrowisata Wingpapuma Hill’s Pujon Serta Kebijakan Strategis Pemerintahan Daerah dalam Mengatasinya - Nahuddin, Yusuf Eko (Bhirawa Law Journal, 2024)
This research aims to identify the obstacles in the development of rural areas and the local government's policies in addressing these obstacles. This research method employs an empirical legal research type with a sociological juridical approach. The research findings indicate that the obstacles in rural area development include limitations in human resources, financial assistance, infrastructure, management, marketing, and profit-sharing systems. To address these obstacles, the local government has adopted strategic policies, including strengthening the synergy between district, sub-district, and village administrations, planning financing effectively and precisely, encouraging the role of stakeholders at the sub-district, district, and Ministry of Village and PDTT levels to provide support in rural area development, and encouraging third parties (local investors) to invest in rural area development by offering incentives related to tax obligations on tax objects under the jurisdiction of the local government.